Extrapulmonary sarcoidosis with a focus on cardiac, nervous system, and ocular involvement. (July 2021) - Belperio, John A.; Shaikh, Faisal; Abtin, Fereidoun; Fishbein, Michael C.; Saggar, Rajan; Tsui, Edmund; Lynch, Joseph P.
Abstract: Sarcoidosis is a poorly understood granulomatous disease that involves the lungs and/or intrathoracic lymph nodes in more than 90% of cases. Although pulmonary sarcoidosis is the leading cause of mortality in this disease, this review focuses on three sites of extrapulmonary involvement (heart, nervous system, and eyes), since involvement of any of these sites can be catastrophic, leading to death, debilitation, or blindness. Patients with cardiac, ocular and neurosarcoidosis necessitate a multidisciplinary approach with careful and long-term follow-up. Prompt diagnosis with imaging and/or biopsy and treatment is required to avoid irreversible damage. Corticosteroids are the mainstay of therapy and are often associated with rapid and durable remissions. Immunosuppressive or biologic agents are reserved for patients failing or experiencing side effects from steroids. Managing sarcoidosis requires vigilance, judgement, and awareness of the vagaries of this fascinating disease.